Development of Track Superelevation Simulation Testing System. Issue 5 (January 2021) - Fu, Huijun; Yang, Jing; Liu, Shihui
Abstract: This paper first discusses the standard requirements and the existing test method for the coefficient of flexibility of the existing metro vehicle. The existing method has the disadvantages of manpower cost, insufficient accuracy of track lifting, different lifting speed of jacks under axle boxes. There are also safety hazards of the vehicle capsizing and the jack sliding. This paper introduces a set of simulation testing system based on hydraulic principle for these problems, measuring track superelevation accurately, reading and controlling the height of vehicle body and the track, thus realizing measuring the coefficient of flexibility. This system has the advantages of simple structure, easy installation, convenient operation and high measuring precision. The track distance, wheelbase and biaxial distance are all variable. It also saves manpower and effectively eliminate safety hazards.